2011
DOI: 10.1111/j.1524-475x.2011.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus‐induced loss of wound strength can be prevented by a short postoperative delay in its administration

Abstract: The use of mammalian target of rapamycin inhibitors coincides with an increased incidence of surgical complications. In previous experiments, serious negative effects of postoperative everolimus on anastomotic strength were found. This study aims to investigate if delayed drug administration can prevent loss of wound strength. Ten groups of Wistar rats each received daily oral doses of 1.0 or 2.0 mg/kg everolimus, starting the day of anastomotic construction in both ileum and colon, or 1, 2, 3, or 4 days later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Using this robust approach, the incidence and duration of wound healing complications at months one and three post‐transplant were found to be similar in the everolimus and MMF arms . Clinical data suggesting that the impairment of wound healing has declined as the intensity of mTOR inhibitor dosing has decreased are consistent with preclinical evidence demonstrating that the effect of mTOR inhibitor on experimental wound healing is dose dependent .…”
mentioning
confidence: 53%
“…Using this robust approach, the incidence and duration of wound healing complications at months one and three post‐transplant were found to be similar in the everolimus and MMF arms . Clinical data suggesting that the impairment of wound healing has declined as the intensity of mTOR inhibitor dosing has decreased are consistent with preclinical evidence demonstrating that the effect of mTOR inhibitor on experimental wound healing is dose dependent .…”
mentioning
confidence: 53%
“…Willems et al showed that loss of wound strength can be prevented by delaying postoperative administration of everolimus 87. In the study by Masetti et al, in which everolimus was initiated 10 days after transplantation, incisional hernias were reported more frequently in the everolimus group than with cyclosporine (46.1% versus.…”
Section: Everolimusmentioning
confidence: 99%
“…In case of a negative effect of MMF on wound strength, it will be interesting to find out if any persistence of the effect is measured when delaying MMF for 3 days, as we have measured in a different experiment with Everolimus, in the same bowel anastomosis model. 18 …”
mentioning
confidence: 99%